Human Capital and Racial Inequality in the US Labor Market - Thompson, Owen (Journal of Economic Literature, 2026)
If racial gaps in measures of human capital like educational attainment and standardized test scores were eliminated, what would happen to racial disparities in wages, employment, and other labor market outcomes?A credible answer to this question is foundational for understanding the nature and scope of racial inequality and discrimination in the United States.This article reviews and synthesizes a literature that studies this question by estimating the extent to which controlling for measures of human capital changes Black-white gaps in labor market outcomes, and discusses various conceptual and methodological issues related to interpreting this type of exercise.I show that while accurately interpreting this exercise and its many variants requires careful thinking, the results elucidate many important and subtle aspects of racial inequality in the United States.